Modeling for Management: A Case Study of the Cañete watershed, Peru - Francesconi, Wendy; Uribe, Natalia; Valencia Gómez, Jefferson; Quintero, Marcela (CRC Press, 2018)
Introduction The Cañete River watershed located in the central Peruvian Andes, is undergoing hydrological changes due to global rising temperatures, landuse changes and increased water supply demand. At the river’s source in the ice-covered mountains at 5,800 m.a.s.l., changes in the landscape are evident given the ever receding snow covered ground. According to aerial photographs of the snowcap mountains, out of the 16 snow peaks that existed in 1962, only 11 remained in 1990 (Cementos Lima S.A.). Exacerbating this situation are the changes in land use occurring at the upper and middle watershed. The watershed’s natural habitat functions as a sponge, retaining much of the water that melts from the glaciers or that falls as precipitation (Wiegers et al., 1999). In addition, lakes, puddles, springs and creeks create a water holding network that transports and slows down water losses along the elevation gradient. Yet, changes in ecosystem dynamics affect the water holding capacity of the watershed, leading to more erratic water flows with longer dry periods and flush events.